The antibacterial and antifungal potential of marine natural ingredients from the symbiont bacteria of mangrove - D. Pringgenies; W. Ari Setyati; F. Feliatra; D. Ariyanto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Mangroves are known to contain tannins, flavonoids, and quinones, which have the potential to be antibacterial, effective even against multidrug-resistant bacteria. Mangroves also have antifungal and antiviral properties. Although, mangroves are known for their use as medicinal ingredients, information regarding symbiont bacteria’s antibacterial and antifungal potential is still scarce. Therefore, this study aimed to examine symbiont bacteria in the fruit and leaves of Xylocarpus granatum as additional raw materials for anti-acne cosmetic creams and moisturisers.METHODS: Symbiont bacteria were isolated using the pour plate method through Zobell 2216E and incubated for 2 x 24 hours at 27.5 Celcius degree. Afterwards, 13 isolates were successfully isolated and characterised based on their morphology. Further, everal tests were conducted, including the antibacterial test, antifungal test, molecular identification, and gas chromatography-mass spectrometry. The pathogenic bacteria used in the antibacterial test were Staphylococcus aureus, Vibrio harveyi, and Vibrio alginolyticusFINDINGS: The antibacterial test results showed that eight isolates were capable of producing an inhibition zone against S. aureus, seven isolates were positive for antibacterial activity against Vibrio harveyi, and 10 isolates were positive for antibacterial activity against Vibrio alginolyticus. The pathogenic fungi used in the antifungal test were Malassezia furfur and Candida albicans. The antifungal test results demonstrated that six isolates could produce inhibition zones against Malassezia furfur and Candida albicans. Furthermore, molecular identification was carried out on six potential isolates based on the antibacterial and antifungal tests, which were X2.52, X1.65, X1.64, X1.53, X1.54, and X1.63. The molecular identification results revealed the occurrence of four species in the Xylocarpus granatum mangroves, namely, Sinomicrobium oceani, Proteus mirabilis, Pseudomonas khazarica, and Alcaligenes aquatilis.CONCLUSION: The study found that the mangrove symbiont bacteria had antibacterial and antifungal potential. The compound with the highest concentration in six isolates was 9-octadecenoic acid, methyl ester. This type of content has antibacterial potential and is also predicted to have antifungal potential.